Dataset extraction from advertising marketplaces: experiences with Facebook, Olx, and Mercadolivre - Diniz, Eduardo; Medeiros de Araújo, Gustavo (Advanced Notes in Information Science, 2022)
Considering the increasing amount of information produced in digital marketplaces, the growing adhesion to these types of services by internet users in Brazil and the world, and the lack of work related to this topic, this research aims to experiment with dataset extraction ads. After analyzing the main e-commerce spaces in Brazil, the chosen marketplaces were: Mercado Livre, Facebook, and OLX. Python's programming language uses the following libraries: scrappy, beautifulsoup, and Selenium Webdriver. After analyzing the web structure of the ad results pages, scripts were created to extract the main variables of the ad within a common category among the marketplaces. The results show that scrapers can remove datasets from advertisements on these platforms in different formats. Such information has potential for exploration in various segments of data science